White Saviors and Noble Savages: Complicating Saviorism, Agency, and Appropriation in Frank Herbert’s 'Dune' - Rodgers, Andrew C. (Tufts Archival Research Center, 2022)
My research engages with critiques of Frank Herbert’s science fiction classic Dune in order to raise questions about the impact of authorial intent and appropriation on the aesthetic and moral value of a work of fiction. In particular, I focus on arguments that the text employs harmful tropes like the white savior, an effortlessly capable protagonist who can save an indigenous population from a plight against which they are helpless, and the noble savage, a romanticized indigenous population with admirable qualities but little capacity for action. With these in mind I examine the text itself alongside paratextual commentary by Herbert to attempt to show that these criticisms are largely based on early interpretations of the text rather than the intent of the author himself. On a similar note I explore questions of cultural appropriation in the text and wonder whether appropriation on its own attaches negative moral value to a work of art. I argue that it does not, but also that consumers should be more conscious of appropriation in works of (especially speculative) fiction. Authors in academia are held to a high standard when it comes to appropriation, whereas similar practices in fiction are often opaque and inaccessible, which can result in the types of misinterpretations that we see in Dune. Both of these topics relate to a concluding discussion about the cultural studies and popular culture which seeks to understand who creates meaning in a piece of art: whether it is the author/creator, an editor, or the audience.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Religion.